2018
DOI: 10.1002/jsfa.9112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shading intensity on morphological and color traits and on chemical components of new tea (Camellia sinensis L.) shoots under direct covering cultivation

Abstract: The morphological traits, color traits, and chemical components of new tea shoots and leaves varied depending on radiation intensity, shoot growth, and cropping season. These findings are useful for covering cultivation with high quality and high productivity in tea gardens. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 38 publications
4
63
1
Order By: Relevance
“…Since the Chl a/b ratio is an index of LL acclimation, we measured Chl a/b ratio in the leaves of shaded tea plants. Chl a/b ratio was significantly lower in shaded leaves than in the control leaves both in the first and second cropping seasons (Figure 1c,d), which was consistent with trends in a previous study of shading treatment of tea plants [11]. This result suggests that shaded tea plants acclimated to LL conditions by increasing the size of light-harvesting antenna.…”
Section: Changes In Chl Content and Chl A/b Ratiosupporting
confidence: 91%
See 2 more Smart Citations
“…Since the Chl a/b ratio is an index of LL acclimation, we measured Chl a/b ratio in the leaves of shaded tea plants. Chl a/b ratio was significantly lower in shaded leaves than in the control leaves both in the first and second cropping seasons (Figure 1c,d), which was consistent with trends in a previous study of shading treatment of tea plants [11]. This result suggests that shaded tea plants acclimated to LL conditions by increasing the size of light-harvesting antenna.…”
Section: Changes In Chl Content and Chl A/b Ratiosupporting
confidence: 91%
“…It has been reported that shading treatment of tea plants increases Chl levels [6][7][8]10,11]. In our experiments, total Chl content was increased by shading treatment, as shown by the data at day 0 in Figure 1a,b.…”
Section: Changes In Chl Content and Chl A/b Ratiosupporting
confidence: 83%
See 1 more Smart Citation
“…Negative prediction accuracy could be an artefact of the mathematical formulas used to calculate correlation coefficients when the expected accuracy is low 44 . One reason for the rather low FAA, Chl, and EGC r levels may be that their phenotypes were susceptible to environmental factors, such as light 45,46 and temperature 47 , and tea management-related processes 48 . Because tea plants are a woody perennial crop; therefore, it is difficult to control these environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Matcha is a powdered type of Japanese green tea (Camellia sinensis) of the Tencha type [12], commonly consumed in the world, and the frequency of its consumption keeps increasing [13]. This tea type is particularly rich in antioxidant compounds due to its traditional way of cultivation [14,15]. Ideally, during most of its growth time [16] it is shaded by natural bamboo fabric [11].…”
Section: Introductionmentioning
confidence: 99%